Band Structure Extraction at Hybrid Narrow‐Gap Semiconductor–Metal Interfaces. Issue 4 (31st December 2020) - Schuwalow, Sergej; Schröter, Niels B. M.; Gukelberger, Jan; Thomas, Candice; Strocov, Vladimir; Gamble, John; Chikina, Alla; Caputo, Marco; Krieger, Jonas; Gardner, Geoffrey C.; Troyer, Matthias; Aeppli, Gabriel; et al.
Abstract: The design of epitaxial semiconductor–superconductor and semiconductor–metal quantum devices requires a detailed understanding of the interfacial electronic band structure. However, the band alignment of buried interfaces is difficult to predict theoretically and to measure experimentally. This work presents a procedure that allows to reliably determine critical parameters for engineering quantum devices; band offset, band bending profile, and number of occupied quantum well subbands of interfacial accumulation layers at semiconductor‐metal interfaces. Soft X‐ray angle‐resolved photoemission is used to directly measure the quantum well states as well as valence bands and core levels for the InAs(100)/Al interface, an important platform for Majorana‐zero‐mode based topological qubits, and demonstrate that the fabrication process strongly influences the band offset, which in turn controls the topological phase diagrams. Since the method is transferable to other narrow gap semiconductors, it can be used more generally for engineering semiconductor–metal and semiconductor–superconductor interfaces in gate‐tunable superconducting devices. Abstract : Detailed understanding of band alignments and band bending profiles in metal–semiconductor heterostructures is critical for the development of quantum computing devices. This work describes a procedure for extraction of the band alignment in buried metal–semiconductor interfaces using angular resolved photoemission spectroscopy.